EFFECTIVE STRATEGIES FOR TEACHING ENGLISH IN PRESCHOOL SETTINGS (Modern education and development, 2025)
This article explores the importance of teaching English in preschool institutions and provides an in-depth look at effective strategies that can be applied in early childhood education. Early exposure to a foreign language not only helps with linguistic development but also improves cognitive and social skills. The article highlights methods such as play-based learning, use of visual aids, Total Physical Response (TPR), and parental involvement. It also emphasizes the teacher’s role in creating a child-friendly and stimulating environment that encourages confidence and participation.